(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Tuberculosis remains a major public health problem with considerable economic burden worldwide. The aim of this study was to estimate the economic burden of tuberculosis in Cyprus during 2009. Methods: A retrospective probabilistic incidence-based cost of illness model was developed to calculate, from the societal perspective, the economic burden of the disease including direct medical costs, direct non-medical costs and indirect costs. The bottom-up approach (person-based data) was used for the calculation of direct costs while for the calculation of indirect costs the approach of human capital was employed. In addition, probabilistic sensitivity analysis with 1000 Monte Carlo simulations was performed in order to calculate a 95% Confidence Interval (CI). Results: Mean per patient cost of tuberculosis in Cyprus in 2009 was estimated at €12,882 (95% CI: €12,747.35 – €12,964.32). Direct medical costs accounted for 83.07% of the overall expenses, €10,675 per patient (95% CI: €10,462.07 – €10,780.59). Total direct non-medical costs of €355 (95% CI: €353.04 – 364.29) accounted for 2.77% of the overall expenses whereas 14.16% of the overall expenses were associated with the indirect cost of €1,820 (95% CI: €1,815.20 – €1,873.65). Conclusion: For the first time in Cyprus, the cost of tuberculosis was estimated using a probabilistic incidence-based cost of illness model. Our study confirms that tuberculosis is an expensive disease for the society. In addition, it provides important information to policy makers for the comprehension of the economic consequences of tuberculosis so as they can draft the national health policy accordingly and strengthen surveillance of the disease.